IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATA PELAJARAN KEWIRAUSAHAAN DI KELAS XII SMK DARUNNAJAH 2 BOGOR - Ahmad Cholil; Abdul Saipon; Irman Sumantri; Ahmad Farid Farid (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2023)
This research was explored in depth from the contextuality aspect of the study, and the research methodology design aspect. With a mixed method design (a combination of qualitative and quantitative methods), the results of data analysis show that the implementation of the CTL concept at SMK Darunnajah II Bogor is carried out by following its main components, namely constructivism, inquiry (finding and solving problems), questioning (asking questions). ), learning community (learning community), modeling (modeling), reflection (reflection), and authentic assessment (authentic assessment). The CTL approach implemented in the entrepreneurship subject at Darunnajah Cipining Vocational School, in addition to teaching students to be more critical in the learning process, to be more active, sensitive, and creative in analyzing issues relevant to entrepreneurship subject matter, teachers also teach students to in the context of the values ​​taught by Islam and internalized at the Darunnajah Islamic Boarding School, namely the principle of mutual benefit, not tyrannizing, and not dominating or harming each other, and intended to build a better life and economy for the ummah. The outline of the results of the analysis of student perceptions regarding the implementation of CTL in the entrepreneurship subject at SMK Darunnajah II Bogor shows that as much as 91.38% of the total respondents stated that the CTL concept was very effective in the context of the relevance of material to everyday life experiences and reflections on learning from problem analysis . Keywords: contextual teaching and learning, reflection, inquiry, learning model.